An exploration of gender and workplace bullying in New Zealand. Issue 8 (3rd June 2020) - Gardner, Dianne; Roche, Maree; Bentley, Tim; Cooper-Thomas, Helena; Catley, Bevan; Teo, Stephen; Trenberth, Linda
Abstract : Purpose: Workplace bullying involves a power imbalance, and despite laws in New Zealand which prohibit discrimination on the grounds of gender, women remain under-represented in top-level roles. The aim of the study was to examine whether gender and role (managerial/non-managerial) were related to the bullying experienced by women and men. Design/methodology/approach: An online survey collected data from 991 (41%) men and 1, 421 (59%) women. The survey provided a definition of bullying and asked participants whether they had been bullied at work. If they replied yes, then follow-up questions asked for the gender and role of the perpetrator. Findings: Women were more likely than men to self-identify as having been bullied. Male employers, senior managers, middle managers, supervisor and peers bullied men and women about equally, whereas women bullied women far more than they bullied men. The largest group of bullies of women were female peers, who rarely bullied male peers, while male peers bullied both genders about equally. Female clients bullied female staff but almost never male staff; male clients bullied both men and women but the numbers were small. Research limitations/implications: These data relied on self-report, and people may be reluctant to identify themselves as targets or may not recognize that the negative behaviours they have been facing amount to bullying. Qualitative data can help explore these issues from societal, organizational and policy perspectives. Practical implications: While men and women may differ in how often they recognize or admit to having been bullied, the gendered nature of power in the workplace is well established and reinforced in the findings here. It is clear that organizational leaders, both male and female, need to understand gender and power imbalance and act as role models. Currently, the authors' findings show that the behaviour of at least some of those at the top of New Zealand organizations needs to improve. Social implications: The problem of bullying at work will not be easy to solve. The solutions lie, not with "fixing" individuals via training, stress management and well-being programmes but with effective systems, procedures, policies and leadership that recognize the power dynamics at work. Originality/value: Little is known at present about the relationships between gender and bullying behaviour. The paper focusses on who bullies whom in the workplace and finds that men tend to bully both men and women while women tend to bully women. Importantly, the authors' works suggest that instead of structural and organizational measures to manage bullying, greater initiatives to manage bullying need to consider how gender and power dynamics interact at work.